2010
DOI: 10.1111/j.1365-2141.2010.08207.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy of undetermined significance: a consensus statement

Abstract: SummaryOn February 25, 2009, a panel of international experts on plasma cell dyscrasia and skeletal disease met to discuss monoclonal gammopathy of undetermined significance (MGUS). This non-malignant B-cell disorder is the most common plasma cell dyscrasia and is associated with an increased risk of developing serious B-cell disorders. Individuals with MGUS also have an increased risk of osteoporosis and osteopenia associated with an increased likelihood of developing fractures especially in the vertebral col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 79 publications
0
95
2
Order By: Relevance
“…12,13 Likewise, MGUS is also common in the general population and its prevalence increases with age. 14,15 Interestingly, Bida et al observed that the prevalence of urticaria in patients with MGUS is lower than in the general population (3.3% vs. 5.9% for a risk ratio of 0.6; P=0.02). 11 The monoclonal protein in MGUS is an IgM isotype in 15-20% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Likewise, MGUS is also common in the general population and its prevalence increases with age. 14,15 Interestingly, Bida et al observed that the prevalence of urticaria in patients with MGUS is lower than in the general population (3.3% vs. 5.9% for a risk ratio of 0.6; P=0.02). 11 The monoclonal protein in MGUS is an IgM isotype in 15-20% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The same thromboprophylactic strategy should be applied in MGUS patients as in other patients, in accordance with clinical guidelines. 31,34 All MM patients who do not have excess risk of bleeding and are treated with thalidomide or lenalidomide in combination with dexamethasone or chemotherapy, should receive thromboprophylaxis. In light of the recent randomized clinical trials, aspirin, LMWH, and fixed, low-dose warfarin seem to be effective in thalidomide-treated patients.…”
Section: Thromboprophylaxis In MMmentioning
confidence: 99%
“…18 MGUS is highly prevalent, progresses to MM in only a small percentage of patients, 19 and there is no known strategy to prevent that progression. 18 Geriatricians should consider a diagnostic work-up for plasma cell disorders only when a reason to suspect one exists. The diagnostic criteria for MM, SMM, and MGUS were recently updated (Box 1).…”
Section: Evaluation and Diagnosismentioning
confidence: 99%